Environmental controls on water use efficiency during severe drought in an Ozark Forest in Missouri, USA - YANG, BAI; PALLARDY, STEPHEN G; MEYERS, TILDEN P; GU, LIAN-HONG; HANSON, PAUL J; WULLSCHLEGER, STAN D; HEUER, MARK; HOSMAN, KEVIN P; RIGGS, JEFFERY S; SLUSS, DANIEL W (Global change biology, 2010)
To accurately predict ecosystem responses induced by climate warming at local-to-global scales, models are in need of more precise knowledge of response during periods of environmental stress such as drought. In this paper, we studied environmental control of canopy-level water use efficiency (WUE) during drought at an eddy flux site in an oak-hickory forest in central Missouri, USA. Two consecutive severe droughts in the summers of 2006 and 2007 afforded coverage of a broad range of environmental conditions. We stratified data to obtain subranges that minimized cross-correlations among putative WUE-controlling factors. Our results showed that WUE was subject to control by atmospheric saturation deficit (ASD), soil water potential (SWP) and the ratio of diffuse to total photosynthetically active radiation (If/It). Generally, WUE was found to scale with 1/(ASD)⁰.⁵, consistent with predictions from stomatal optimization theory. In contrast, SWP and If/It were related to WUE in a linear fashion. ASD was better correlated with WUE than either of the other two factors. It was also observed that the relationship between WUE and any single controlling factor was subject to influence of the other two. One such example was an opposite response of WUE to SWP between low and high ASD values, suggesting a breakdown of stomatal optimality under severe environmental stresses and a shift from optimal stomatal regulation to nonstomatal regulation at leaf scale. We have demonstrated that different data handling (stratified vs. nonstratified) or selection (hourly vs. daily) could lead to different conclusions on the relationship between WUE and its controls. For this reason, we recommend modelers to be cautious when applying WUE-response formulas at environmental conditions or at time scales different from those at which they are derived.